Next-generation sequencing reveals frequent consistent genomic alterations in small cell undifferentiated lung cancer. Issue 9 (24th June 2014) - Ross, J S; Wang, K; Elkadi, O R; Tarasen, A; Foulke, L; Sheehan, C E; Otto, G A; Palmer, G; Yelensky, R; Lipson, D; Chmielecki, J; Ali, S M; et al.
Abstract : Aims: Small cell lung cancer (SCLC) carries a poor prognosis, and the systemic therapies currently used as treatments are only modestly effective, as demonstrated by a low 5-year survival at only ∼5%. In this retrospective collected from March 2013 to study, we performed comprehensive genomic profiling of 98 small cell undifferentiated lung cancer (SCLC) samples to identify potential targets of therapy not currently searched for in routine clinical practice. Methods: DNA from 98 SCLC was sequenced to high, uniform coverage (Illumina HiSeq 2500) and analysed for all classes of genomic alterations. Results: A total of 386 alterations were identified for an average of 3.9 alterations per tumour (range 1–10). Fifty-two (53%) of cases harboured at least 1 actionable alteration with the potential to personalise therapy including base substitutions, amplifications or homozygous deletions in RICTOR (10%), KIT (7%), PIK3CA (6%), EGFR (5%), PTEN (5%), KRAS (5%), MCL1 (4%), FGFR1 (4%), BRCA2, (4%), TSC1 (3%), NF1 (3%), EPHA3 (3%) and CCND1. The most common non-actionable genomic alterations were alterations in TP53 (86% of SCLC cases), RB1 (54%) and MLL2 (17%). Conclusions: Greater than 50% of the SCLC cases harboured at least one actionable alteration. Given the limited treatment options and poor prognosis of patients with SCLC, comprehensive genomic profiling has the potential to identify new treatment paradigms and meet an unmet clinical need for this disease.